Time‐lapse geophysical assessment of agricultural practices on soil moisture dynamics - Blanchy, G. (2021)
Assessing the impact of agricultural practices through the growth season can reveal important information for the crop production. In this work, we demonstrate the use of time‐lapse electrical resistivity tomography (ERT) and electromagnetic induction (EMI) surveys through a series of three case studies illustrating common agricultural practices (cover crops, compaction with irrigation, and tillage with N fertilization). In the first case study, time‐lapse EMI reveals the initial effect of cover crops on soil drying and the absence of effect on the subsequent main crop. In the second case study, compaction leading to a shallower drying depth for potatoes (Solanum tuberosum L.) was imaged by time‐lapse ERT. In the third case study, larger changes in electrical conductivity over time were observed in conventional tillage compared with direct drill using time‐lapse EMI. In addition, different N application rates had a significant effect on the yield and leaf area index but only ephemeral effects on the dynamics of electrical conductivity, mainly after the first application. Overall, time‐lapse geophysical surveys show great potential for monitoring the impact of different agricultural practices that can influence crop yield.